(3JeGe aUjM GdcdGes - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3eQh GdTGgMGf s)
(3ChdgG (B:s
(3bGd CMeO Hf aGQS gPG cJGH JeGe aUjM GdcdGe s
(3BNQgG (B:s
(3bGd CMeO Hf aGQS gPG BNQ eG CQOJ EKHGJg ai gPG GdHGH hMbG Cbhd Ef LejY eG PcQJg aef Yde CHj GdYHGSq s
(3Vef eLehY , JQJjHgG (B: 2s
(3HBNQgG fbd ef cJGH dMf GdYGeI dCHi MGJe GdSLSJGfi ai hQbJjfs
(3YdjgG ebGHdIs
(3efbhdI ef NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs